Relationship of Predisposing Factors with Breast Care in Pregnant Women in Sungai Orosan Village Padang Bolak District North Law - Wiwi Wardani Tanjung; Nurhanifah Siregar; Tetty Misbah (International Journal of Basic and Applied Science, 2022)
Breast care needs to be done by pregnant women to be able to expedite the release of breast milk. Most pregnant women do not do breast care because of lack of knowledge in breast care itself, lack of information about breast care such as not protruding nipples, or flat, because of the condition of the breasts, especially the nipples. The purpose of this study was to determine the relationship between predisposing factors and breast care for pregnant women in Sungai Orosan Village, Padang Bolak District, North Padang Lawas Regency in 2021. The type of research was quantitative with a cross sectional study design. The population in this study were all pregnant women as many as 36 people. The sample in this study was all pregnant as many as 36 people. Data were analyzed by univariate and bivariate using Chi Square test. The results showed that there was a relationship between knowledge factors (p= 0.004), parity (p= 0.004) and employment status (p= 0.003) with breast care in pregnant women. The conclusion is that there is a relationship between knowledge, parity and employment status with breast care in pregnant women. It is hoped that pregnant women can increase their knowledge about breast care.